Talaqqi Method in Learning Tahfidz Al-Qur'an at Islamic Elementary School - Intan Setyowati; Mansur Mansur (Pusat Studi Penelitian dan Evaluasi Pembelajaran, 2024)
The talaqqi method is one methode that is sitable for use by early chilhood in memorizing the Qur'an, but in reality students are stiil found to be less focused in memorizing because learning tahfidz is boring and sometimes teachers are less observant in paying attention to student reading. This study examines the talaqqi method in grade 1 studentsin learning al-Qur'an. The purpose of this research isto find the steps, obstacles and solution of talaqqi method in grade 1 students in learning Tahfidz Al-Qur'an in elementary Plus Tahfizhul Quran Annida and elementary Tahfidzul Qur'an Hati Beriman Salatiga City. This research is a qualitative research. After conducting research, it appears that the implementation of the method talaqqi in learning Tahfidz Al-Qur'an, classroom conditioning, student moods, there are some students who cannot read the qur'an in accordance with recitation, is it difficult to control memorization due to time constraints, teachers in learning do not provide innovation, different student abilities, student discipline in murojaah at home.